2009
DOI: 10.1073/pnas.0903994106
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell response to stiffness exhibits muscle-like behavior

Abstract: Living cells sense the rigidity of their environment and adapt their activity to it. In particular, cells cultured on elastic substrates align their shape and their traction forces along the direction of highest stiffness and preferably migrate towards stiffer regions. Although numerous studies investigated the role of adhesion complexes in rigidity sensing, less is known about the specific contribution of acto-myosin based contractility. Here we used a custom-made single-cell technique to measure the traction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
257
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(304 citation statements)
references
References 41 publications
45
257
1
1
Order By: Relevance
“…Contractile cells such as fibroblasts, myoblasts, and platelets have been shown to individually generate contractile forces ranging from 0.1 to 300 nN/cell (1,18,37,38). The accumulation of force generated by these individual active contractile cells results in a macroscopic contraction of the matrix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contractile cells such as fibroblasts, myoblasts, and platelets have been shown to individually generate contractile forces ranging from 0.1 to 300 nN/cell (1,18,37,38). The accumulation of force generated by these individual active contractile cells results in a macroscopic contraction of the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments showed that contractile cells (e.g., fibroblasts) subjected to uniaxial loading have an active stress versus strain-rate response that obeys the classic Hill relation (18,28). As in other contractile cells, contraction in platelets involves myosin-actin interactions (29).…”
Section: Properties Of Constitutive Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 a) and a stiffer endothelium also impedes transmigration. Although the modulus of the ECM ðm t Þ has little influence on the resistance force, it has a strong effect on the actomyosin contractile forces: at the same chemomechanical coupling level, a softer ECM induces lower levels of cellular contractile force (21,26,27), which may not be sufficient for the cells to overcome the resistance force. Therefore, it is less likely for the cell to transmigrate when the ECM is soft (Fig.…”
Section: Ecm Stiffness and Gap Size Modulate Nuclear Transmigrationmentioning
confidence: 99%
“…A number of cells such as fibroblasts, cardiomyocytes, epithelial cells, endothelial cells and smooth muscle cells develop significant contractile forces as part of their physiological function [9][10][11][12]. One important function of cellular forces is to act on the surrounding extracellular matrix (ECM), align the matrix and reorganize tissues as they form and develop.…”
Section: Introductionmentioning
confidence: 99%